Optimalisasi Pengalaman Pengguna: Redesain Website Sinau Digital Universitas Negeri Surabaya dengan Usability Principles Menggunakan Figma - Rizki Bani Adam, Khoiru; Avlach, Tazkiyah; Amelinda, Nesya; Aji Nur Khairi, Berlian; Faizah, Faizah (Jurnal Etnik: Ekonomi-Teknik, 2023)
In the era of globalization, each university now has a website that represents them. At Surabaya State University, they had the UNESA Sinau Digital website. The study aims to evaluate the quality of the Unesa Digital Sinau website through user evaluation. The main problem faced by this website is its less user-friendly appearance and navigation. Therefore, the study uses a method of collecting quantitative data by collecting online questionnaire data from students of Surabaya State University, and the Evaluation of Usability Principles revealed a number of problems, including less intuitive navigation and impeccable layout. It also refers to the human aspect, which refers to psychological, physiological, and behavioral theories of human-computer interaction. Through a redesign based on usability principles laid down by Nielson and Molich, there is a significant improvement in the user experience, learning efficiency, and user satisfaction. Improvements include improved layouts, attractive visual designs, and the addition of features that facilitate access and interaction. The application of usability principles on UNESA's Digital Sinau website has a positive impact on student academic development, user retention, and university image. By continuing to prioritize usability, UNESA Digital Sinau can continue to support the development of education in the growing digital age.